PERBANDINGAN STATUS KESUBURAN TANAH DI DUA DATARAN TINGGI: STUDI KASUS DESA DOULU (BERASTAGI) DAN DESA NALELA (TOBA) - SIrait, Mareben; Sirait, Tania; Sahfitra, Angga Ade; Rannando, Rannando; Tarigan, Raudha Anggraini (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
This study aims to disseminate the soil fertility status of two types of agricultural land, namely shallot cultivation land in Doulu Village, Berastagi District, Karo Regency, and rice field land in Nalela Village, Porsea District, Toba Samosir Regency, North Sumatra Province. The research methods used include field surveys, random soil sampling, and laboratory analysis of soil physical and chemical properties, including pH, cation exchange capacity (CEC), base saturation (KB), organic C content, nitrogen (N), phosphorus (P), potassium (K), and other nutrients such as calcium (Ca) and magnesium (Mg). The results showed that the analysis of shallot land in Doulu Village had a moderate to low level, due to acidic pH, low levels of organic matter, nitrogen, and phosphorus, and suboptimal cation exchange capacity. Meanwhile, rice fields in Nalela Village showed very acidic pH, low to very low quality CEC and organic C, and low phosphorus and potassium content. Based on the land suitability evaluation, agricultural land in both areas is categorized in class S2 (quite suitable) to S3 (marginally suitable), which indicates the need for land management intervention. This study recommends the application of balanced fertilization, addition of organic matter, improvement of soil pH, and erosion management to improve soil fertility status and support the sustainability of agricultural production in both villages.